The perception of nested affordances: An examination of expert climbers. (January 2021) - Seifert, Ludovic; Dicks, Matt; Wittmann, Frieder; Wolf, Peter
Abstract: Nested affordances in climbing comprise of multiple sequential actions, encompassing more than isolated reaching and grasping. This study examined the extent to which the perception of (multiple) nested affordances in climbing can be understood relative to body-scaled anthropometrics (arm span) and action-scaled (maximal action capabilities) measures, in relation to sequential task-goals of varying complexity. The utilisation of functionally equivalent actions during the actualisation of nested affordances was also investigated. Participants were required to estimate the maximal distance a handhold could be reached in four conditions of varying complexity: nested affordances (reach to Touch ; reach to Grasp ) vs. multiple nested affordances (reach to grasp with one hand followed by Removing the other hand from the starting handhold; reach to grasp with one hand followed by Moving up to another handhold). Ten expert climbers first had to estimate their maximal reaching distance in these different conditions ( Touch, Grasp, Remove, Move Up ) before performing the climbing movement. This sequence of estimation-action was repeated four times in each condition. Results revealed that action-scaling measures better captured nested affordances when multiple sequential behaviours are nested than body-scaled measures. Our findings also suggest that expert climbers utilise functionally equivalent movements during the realisation of multiple nested affordances ( Remove and Move Up conditions). Highlights: Climbers estimate accurately their maximal action capabilities. Climbers act near their maximal action capability regardless of affordances complexity. Action-scaling relations better captured 'more than two' nested affordances than body-scaled measures. Climbers utilise functionally equivalent movements when performing 'more than two' nested affordances.